Field evaluation of a mobile biosafety laboratory in Senegal to strengthen rapid disease outbreak response and monitoring - Cheikh Fall (African Journal of Laboratory Medicine, 2020)
Background: Past and recent outbreaks have highlighted the vulnerability of humans to infectious diseases, which represent serious economic and health security threats. A paradigm shift in the management of sanitary crises is urgently needed. Based on lessons from the 2014 Ebola outbreak, the Praesens Foundation has developed an all-terrain mobile biosafety laboratory (MBS-Lab) for effective field diagnostics capabilities.